Depth-dependent stabilization mechanisms of soil organic carbon and total nitrogen in different mixed modes of subtropical Moso bamboo forests - Yan, Lingyuan; Gao, Decai; Wang, Huimin; Meng, Shengwang; Lin, Gang; Fu, Jingying (Frontiers in Microbiology, 2025)
Forest soils play a pivotal role in terrestrial carbon (C) sequestration and nitrogen (N) cycling, particularly in subtropical Moso bamboo (Phyllostachys edulis) forests ecosystems. While prior studies have explored soil organic carbon (SOC) and total nitrogen (TN) dynamics in bamboo systems, the depth-dependent stabilization mechanisms governing these stocks under contrasting mixed-species regimes remain unresolved, limiting predictions of long-term C/N storage. Here, we investigated SOC and TN in stratified soil samples (0–100 cm) across three forest types in southeastern China: pure Moso bamboo (Mb), mixed Moso bamboo-evergreen broadleaved (MbB), and mixed Moso bamboo-Chinese fir (Cunninghamia lanceolata) (MbF) forests. Results showed that SOC and TN stocks showed no significant differences between MbB and Mb across all soil layers (0–20, 20–40, 40–60, 60–80, and 80–100 cm) or within the entire 0–100 cm soil profile. While soils (0–100 cm) in MbB exhibited enhanced enzyme activity (β-glucosidase: +52%; N-acetyl-glucosaminidase: +89%) and ammonium availability (+47%) compared to Mb, equivalent SOC and TN stocks across 0–100 cm profiles revealed microbial priming effects and stoichiometric constraints offsetting litter-derived C gains. In contrast, MbF displayed substantial TN depletion (−32% vs. Mb) across the entire 0–100 cm soil profile with parallel SOC/TN reductions in subsurface layers (20–40 cm: −42% SOC, −48% TN), driven by coniferous lignin inputs and microbial N mining, no significant differences were detected in the 0–20, 40–60, 60–80 or 80–100 cm layers. Vertical stratification analysis demonstrated shifting regulatory controls: microbial biomass dominated surface SOC/TN stabilization, while inorganic N dynamics and enzymatic activities controlled deeper horizons. These findings establish that SOC stability emerges from depth-specific enzyme-microbe-mineral interactions, while TN stocks reflect microbial stoichiometric adaptation to litter chemistry - critical insights for optimizing mixed-species strategies in bamboo forest management.